(untitled) (Tribhuvan University Journal of Food Science and Technology, 2022)
This research studies the effect of different pretreatment conditions on dehydration characteristic of milky white mushroom (Calocybe indica). Mushroom samples were dried using three different methods (cabinet drying, solar drying and sun drying) with different pretreatments such as blanching (85° for 1 min), sulfiting (0.3% KMS for 10 min) and blanching and sulfiting and untreated. After dehydration, differently pretreated products from each drying mechanisms were analyzed for proximate composition, drying rate, rehydration properties, and sensory qualities. Among different pretreatments in all three drying mechanisms (cabinet, sun and solar), sulfited samples showed the best result in terms of nutrients retention such as crude protein (23.17 g/100 g, 22.57 g/100 g, 21.91 g/100 g), crude fat (5.01 g/100 g, 4.47 g/100 g, 4.21 g/100 g) and crude fibre (13.62 g/100g, 13.11 g/100g, 12.04 g/100 g) respectively. Blanched and sulfited samples showed satisfactory results on drying time (8 h, 9 h, 10 h) to reach constant moisture level, rehydration ratio (3.16, 2.54, 2.81), rehydration coefficient (0.47, 0.41, 0.42), and percent water in rehydrated mushroom (69.62%, 62.45%, 65.55%) respectively. Likewise, among different drying mechanisms, cabinet dried sample was found to be superior in terms of nutrients retention (crude protein 23.17 g/100 g; crude fat 5.01 g/100 g; and crude fibre 13.62 g/100 g), drying time (8 h) and rehydration properties (rehydration ratio 3.16; rehydration coefficient 0.47; and percent water in rehydration mushroom 69.2%).